EXTRACTION OF RESIDUAL GLYCERIDES FROM FATTY ACIDS PRODUCED BY PALM OIL LIPOLYSIS - Rizka Fadhillah, Dinda
The technology of palm oil lipolysis that release up to 70% free fatty acids is being developed at the Chemical Engineering Department of Institute of Technology Bandung. Technology for separating the lipolysis products into fatty acids and residual glycerides (mostly monoglycerides) has also to be developed in order to compose a technological package of fatty acids supply for the production of green diesel and biogasoline from fatty acids via decarboxylation and pyrolysis of the divalent basic metal soaps.